Financial instruments of anti-inflationary regulation: comparative analysis and priorities for Russian economic policy ("Journal "U". Economy. Management. Finance.", 2025)
The article analyzes financial instruments of anti-inflation regulation used in global and Russian practice. Particular attention is paid to the comparative assessment of monetary and fiscal policies in Russia, the United States and the EU during 2019–2023. The article identifies the specific effects of key interest rates and budget measures on inflation in different economic environments. Recommendations are made to improve the efficiency of Russia’s anti-inflation policy, including economic diversification and digitalization. Proposed approaches aim to ensure sustainable growth and reduce inflationary risks amid global instability.
Keywords: inflation; monetary policy; fiscal instruments; regulation; Russia; international experience